Pengaruh Pengunaan Media Sosial dan Pendidikan Kewirausahaan Terhadap Minat Berwirausaha Pada Mahasiswa FKIP Universitas PGRI Mahadewa Indonesia - Cahayani, Ni Luh Putu; Westra, I Ketut; Ariyati, Ni Made; Netriani, Ni Komang; Sau, Teldi Sumarno Boling (Jurnal Pendidikan Ekonomi Undiksha, 2022)
Entrepreneurship Education is a subject that must be taken by students in the teaching and education faculty. However, interest in entrepreneurship is still in the low category. This study aims to determine whether or not there is an influence of social media and entrepreneurship education on students' interest in entrepreneurship. Data collection techniques using observation, interviews, documentation, and questionnaires with linear regression analysis testing two predictors and determination test. The results showed that (1) the use of social media variables influenced the interest in entrepreneurship with a t-count value of 7.652 which was greater than the t-table value of 2.010 with a sig value of 0.000 <0.05; (2) the entrepreneurship education variable has an effect on the interest in entrepreneurship with a t-count value of 10.375 which is greater than the t-table value of 2.010 with a sig value of 0.000 <0.05; (3) the variables of the use of social media and entrepreneurship education have a significant effect on interest in entrepreneurship with an F-count value of 54.611 which is greater than the F-table value of 3.187 with a sig value of 0.000 <0.05; (4) the results of the coefficient of determination using the Adjusted R Square method state that the use of social media and entrepreneurship education has an effect on interest in entrepreneurship with a value of 67.8% while the remaining 32.2% is influenced by other factors not included in the research model